2012
DOI: 10.1158/1535-7163.mct-11-1020
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor Activity of Src Inhibitor Saracatinib (AZD-0530) in Preclinical Models of Biliary Tract Carcinomas

Abstract: Biliary tract carcinoma (BTC) has a poor prognosis due to limited treatment options. There is, therefore, an urgent need to identify new targets and to design innovative therapeutic approaches. Among potential candidate molecules, we evaluated the nonreceptor tyrosine kinase Src, observing promising antitumor effects of its small-molecule inhibitor saracatinib in BTC preclinical models. The presence of an active Src protein was investigated by immunohistochemistry in 19 surgical samples from patients with BTC.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…Figure 4a–d shows that the wound in MT-CHC01 cells was significantly closed at 24, 48, and 72 h after the wound; the migration potential of MT-CHC01 is lower if compared to other commercial cell lines such as HuH28 (Fig. 4e), that closes the wound within 24 h as previously demonstrated [ 38 ]. This data was confirmed by transwell chamber assay (Fig.…”
Section: Resultssupporting
confidence: 71%
“…Figure 4a–d shows that the wound in MT-CHC01 cells was significantly closed at 24, 48, and 72 h after the wound; the migration potential of MT-CHC01 is lower if compared to other commercial cell lines such as HuH28 (Fig. 4e), that closes the wound within 24 h as previously demonstrated [ 38 ]. This data was confirmed by transwell chamber assay (Fig.…”
Section: Resultssupporting
confidence: 71%
“…A previous study indicated that about 80% of BTC specimens expressed an activated Src protein similar to other malignancies (3)(4)(5)(6)18). In our study, a total of nine BTC cell lines were tested, and the IC 50 values ranged from 0.63 to 4.45 mmol/L in 3-day MTT assays.…”
Section: Discussionmentioning
confidence: 83%
“…A recent study demonstrated that Src is also frequently overexpressed in BTC as in other malignant diseases, although its relationship with clinicopathologic parameters or histologic origin was not significant (18). In addition, blocking Src activity by novel Src inhibitors such as saracatinib (AZD-0530) and AZM555130 reduced the proliferative and invasive potential of human BTC cell lines (18,19).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several Src kinase inhibitors such as bosutinib, dasatinib, and ponatinib have been developed and approved as anticancer drugs by the United States Food and Drug Administration. However, the therapeutic efficacies of Src inhibitors as single agents in treating various solid tumors are not encouraging, due to the intrinsic complexity of Src signaling and the redundant pathways involved in tumor development [41][42][43][44][45]. Therefore, the development of diagnostic markers is urgently needed for the preselection of potential responders to anti-Src therapy to enhance clinical benefits.…”
Section: Discussionmentioning
confidence: 99%